A preliminary study on arthropods as potential biological control agents for management of alien ornamental plants in Turkey - Uludag, Ahmet; Arslan, Zübeyde Filiz; Kütük, Halil; Jabran, Khawar (Acta herbologica, 2022)
Alien ornamental plants have the potential to become invasive and biological control is considered a promising method to manage them. Global literature were searched to find out the potential agents for 56 ornamental plants that have invasion potential in Turkey. Out of the biological agents, we compiled the species already in Turkey and could be utilised in managing the invasive species. Moreover, the succesfull biological control agents for these plants in other parts of the world have also been listed. As a result, 128 species of arthropods were found as natural enemies and 27 of them were established in the released areas in the world. In Turkey, out of these 128 species, 58 were noted as present in Turkey, however, their impacts on plants have not been studied in detail. Potential biological agents to control invasive plants in Turkey are: Carpomyia vesuviana Costa for Ziziphus mauritiana Lam., Rhizaspidiotus donacis Leonardi for Arundo donax L., Unaspis euonymi (Comstock) for Euonymus fortunei (Turcz.) Hand.-Mazz., Diaspis echinocacti (Bouché) for Opuntia ficus-indica (L.) Miller, Eulecanium ciliatum (Douglas), Lepidosaphes ulmi (Linnaeus), Melanaspis inopinata (Leonardi) and Phenacoccus aceris (Signoret) for Acer negundo L. There was a possibility to use these biological agents for controlling the alien ornamental plants in Turkey, although there is a need for further Pest Risk Assesment to decide invasiveness of alien plants in Turkey and studies are also required for safe release of beneficial insects.